Pet ownership and mental health in United States adults during COVID-19 - Marcial-Modesto, Dolores; Chin, Brian N.; Casserly, Elizabeth D.; Parsons, Shelby M.; Feeney, Brooke C. (Frontiers in Psychology, 2023)
The COVID-19 pandemic was associated with declines in mental health and increased interest in pet ownership. We aimed to extend past theories and research linking pet ownership and mental health by investigating whether pet ownership was associated with mental health during the initial phases of the COVID-19 pandemic in a sample of American adults. We also tested whether the association of pet ownership and mental health was moderated by relationship status. Participants were 2906 American adults who were recruited for an online survey study between May 2020 and May 2021. Pet ownership was assessed via dichotomous self-report (yes/no) and mental health was assessed using a 13-item questionnaire. The sample was 69.2% female with an average age of 46.0 years. 36.1% of the sample owned a pet and 68.5% of the sample was currently partnered. There was no overall association of pet ownership and mental health during the COVID-19 pandemic (estimated mean difference (EMD)=0.35, 95CI=-0.10,0.80, p=.12). However, we found evidence for an association that was moderated by relationship status. Pet ownership was associated with better mental health among partnered individuals (EMD=0.76, 95CI=0.21,1.30, p=.006). There was no association of pet ownership and mental health among unpartnered individuals (EMD=-0.41, 95CI=-1.20,0.37, p=.30). Our findings suggest that relationship status may represent a critical moderator of the link between pet ownership and mental health. Future studies are needed to identify specific mechanisms of pet ownership that could explain its varied impact on the mental health of partnered and unpartnered individuals.